Evaluation of the Vitek 2 ID-GNB Assay for Identification of Members of the Family Enterobacteriaceae and Other Nonenteric Gram-Negative Bacilli and Comparison with the Vitek GNI+ Card - O'Hara, Caroline M. (American Society for Microbiology, 2003)
We evaluated the Vitek 2 ID-GNB identification card (bioMérieux, Inc., Durham, N.C.) for its ability to identify members of the family Enterobacteriaceae and other gram-negative bacilli that are isolated in clinical microbiology laboratories. Using 482 enteric stock cultures and 103 strains of oxidase-positive, gram-negative glucose-fermenting and nonfermenting bacilli that were maintained at −70°C and passaged three times before use, we inoculated cards according to the manufacturer's directions and processed them in a Vitek 2 instrument using version VT2-R02.03 software. All panel identifications were compared to reference identifications previously confirmed by conventional tube biochemical assays. At the end of the initial 3-h incubation period, the Vitek 2 instrument demonstrated an accuracy of 93.0% for the identification of enteric strains; 414 (85.9%) were correctly identified at probability levels ranging from excellent to good, and an additional 34 (7.1%) strains were correctly identified but at a low level of discrimination. Nineteen (3.9%) strains were unidentified, and 15 (3.1%) were misidentified. The 19 unidentified strains were scattered among 10 genera. Three of the 15 misidentified strains were lactose-positive Salmonella spp. and were identified as Escherichia coli; another was a lactose-positive, malonate-negative Salmonella enterica subsp. arizonae strain that was identified as E. coli. Of the 103 glucose-fermenting and nonfermenting nonenteric strains, 88 (85.4%) were correctly identified at probability levels ranging from excellent to good, and 10 (9.7%) were correctly identified, but at a low level of discrimination, for a total of 95.1% accuracy with this group. Two strains were unidentified and three were misidentified. The errors occurred for strains in three different genera. With the increased hands-off approach of the Vitek 2 instrument and accuracies of 93% for the identification of enteric organisms and 95.1% for the identification of nonenteric organisms with the ID-GNB card, use of this product presents an acceptable method for the identification of most gram-negative organisms commonly isolated in the clinical laboratory. A comparison of these results to those obtained by testing 454 of the same strains with the Vitek GNI+ card revealed no significant difference in the abilities of the two cards to identify these organisms accurately.